2009
DOI: 10.1214/09-aap607
|View full text |Cite
|
Sign up to set email alerts
|

A dual characterization of self-generation and exponential forward performances

Abstract: We propose a mathematical framework for the study of a family of random fields-called forward performances-which arise as numerical representation of certain rational preference relations in mathematical finance. Their spatial structure corresponds to that of utility functions, while the temporal one reflects a Nisio-type semigroup property, referred to as self-generation. In the setting of semimartingale financial markets, we provide a dual formulation of selfgeneration in addition to the original one, and sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
136
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(136 citation statements)
references
References 35 publications
0
136
0
Order By: Relevance
“…We do this because different cases for the domain and range of the functions u and h require appropriately modified and computationally tedious arguments which, if presented at this point, would obscure the clarity of the presentation. It is shown in section 4 (see Propositions 10,14,15,and 19) that there exists a one-to-one correspondence (modulo normalization constants) between increasing and strictly concave solutions to (14) with strictly increasing solutions to (19). It is also shown that the latter can be represented in terms of the bilateral Laplace transform of a positive finite Borel measure, denoted throughout by ν.…”
Section: Monotone Performance Processes and Their Optimal Wealth And mentioning
confidence: 98%
See 2 more Smart Citations
“…We do this because different cases for the domain and range of the functions u and h require appropriately modified and computationally tedious arguments which, if presented at this point, would obscure the clarity of the presentation. It is shown in section 4 (see Propositions 10,14,15,and 19) that there exists a one-to-one correspondence (modulo normalization constants) between increasing and strictly concave solutions to (14) with strictly increasing solutions to (19). It is also shown that the latter can be represented in terms of the bilateral Laplace transform of a positive finite Borel measure, denoted throughout by ν.…”
Section: Monotone Performance Processes and Their Optimal Wealth And mentioning
confidence: 98%
“…2 From a different perspective, one could seek an axiomatic construction of a forward performance process. Results in this direction, as well as on the dual formulation of the problem, can be found in [19] for the exponential case (see, also, [1] for a constrained case). We refer the reader to [10] for further discussion on the forward performance and its similarities to and differences from the classical value function.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…The model therein is incomplete binomial and the initial data is taken to be exponential. The exponential case was subsequently and extensively analyzed in [71] and [95].…”
Section: The Forward Formulationmentioning
confidence: 99%
“…This class of forward performance processes is analyzed in detail in [71] (see, also, [95]). Case 2: Let = ; > 1: Then (38) yields h (x; t) = 1 e The optimal wealth and portfolio processes are given, respectively, by…”
mentioning
confidence: 99%